Professional Competence of Teachers in the Islamic Religious Education Learning Process - Suryani, Lili; Ridwan, Ahmad; Yunus, Abdullah (Yayasan Rahmat Islamiyah, 2025)
This study aims to determine the professional competence of teachers in the learning process of Islamic Religious Education at Baiturrahim Junior High School, Jambi City. This type of research is field research with a qualitative approach through descriptive methods. Data collection techniques include interviews, observation and documentation, while data analysis uses data reduction, data presentation and conclusion drawing. The results of the study indicate that the learning process of Islamic Religious Education at Baiturrahim Junior High School, Jambi City is carried out through the planning, implementation, and evaluation stages. Teachers' professional competence is already visible in several aspects, but has not been fully achieved so that it cannot be said to have complete professional competence.